Functional Imaging: Is the Resting Brain Resting? - Miall, R. Chris (Curr Biol, 2006)
It is often assumed that the human brain only becomes active to support overt behaviour. A new study challenges this concept by showing that multiple neural circuits are engaged even at rest. We highlight two complementary hypotheses which seek to explain the function of this resting activity.